Wybrane zagadnienia prawnej ochrony dziedzictwa kulturowego w krajach Unii Europejskiej - Łukaczyński, Jakub (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The aim of the article is to present selected law institutions and to outline systems for legal protection of cultural goods in several European Union countries, i.e. Belgium, the Czech Republic, France and Spain. The author subjects them to a general analysis ranging from constitutional to legislative instruments, and attempts to compare them to Polish solutions and define their systemic characteristics. The choice of both the countries and the material is related to student cooperation carried out at the University of Gdańsk under the Erasmus Programme.
Keywords: prawna ochrona dziedzictwa kulturowego; Unia Europejska; konstytucyjna ochrona dziedzictwa kulturowego w Republice Czeskiej; ochrona dziedzictwa kulturowego we Francji; hiszpańska konstytucja i dziedzictwo narodowe; polska ochrona dziedzictwa kulturowego